Le patrimoine architectural colonial dans la région du Hodna, un héritage en voie de disparition. Cas de la ville de M’sila en Algérie - Hynda Boutabba; Abdallah Farhi; Mohamed Mili (L’Année du Maghreb)
By choosing to conserve some elements of the past, societies attest to their symbolic value. But for societies that have been colonized, collective memory has trouble to recognizing the colonizer’s legacy. This latter represents a painful episode for community life, generally recalling hostility and political, economical and cultural submissionn. Having lived under French colonial administration, and experienced the clash of civilizations with the West, Algerians assimilate heritage with authenticity going so far as to consider the one as a system of protection against the other (Mechta, 1991; Gharbi, 2001). In this way the former colonial city of M’sila struggles to position itself among objects recognised as part of the cultural heritage of the present city. Like many cities driven by accelerated and uncontrolled urban development, former colonial cities and historic urban centres in Algeria offer heterogeneous urban profiles that are difficult to read and often contradictory. In such cities, the trend is toward repetition of urban architecture and styles as a form of substitution without reference to the specifics of colonial town planning. The present paper offers a study of the colonial centre of M’sila: The Edhahra neighborhood. The neighbourhood is presented in its urban and architectural specificities and evaluated in terms of the urban renewal underway, indentifying the causes of conceptual and stylistic deletions of urban colonial legacy.